The Gale encyclopedia of neurological disorders - Chamberlin, Stacey L.; Narins, Brigham 1962-.; Gale Group (Detroit, Mich. Thomson Gale, 2005)
Provides in-depth coverage of neurological diseases and disorders, including stroke, multiple sclerosis, Parkinson disease, Tourette Syndrome, Alzheimer's disease, cerebral palsy, vertigo, amnesia, and epilepsy, targeted to patients, their families and allied health students. Related topics include communication aids, electric personal assistive mobility devices, medications, and the needs of Alzheimer patient caregivers among others.
List of entries -- Introduction -- Advisory board -- Contributors -- Volume 1: A-L -- Volume 2: M-Z -- Glossary -- General index.
Electronic reproduction.
Keywords: Neurology -- Encyclopedias; Nervous System -- Degeneration -- Encyclopedias; Electronic books